Implementation of Boyolali Regulation Number 18 of 2016 Concerning Street Vendor Regulation - Zulfa Asdiqi; Nuria Siswi Enggrani (Universitas Muhammadiyah Surakarta, 2026)
The existence of street vendors (PKL) in Boyolali Regency plays an important role in the community's economy, thus requiring regulation through regional policies to continue to support economic activities while maintaining order in public spaces. This study aims to analyze the conformity of Boyolali Regency Regional Regulation Number 18 of 2016 with the principles of establishing statutory regulations, as well as to examine the efforts of the Department of Industry and Trade in overcoming obstacles to the arrangement and empowerment of street vendors in Boyolali Regency. This study uses a qualitative descriptive method by examining Boyolali Regional Regulation No. 18 of 2016 through analysis of legal documents and data from the local government and related parties. The results of the study indicate that Regional Regulation No. 18 of 2016 has basically fulfilled the philosophical, sociological, and juridical foundations in the formation of regional regulations, however, several provisions still need to be adjusted to regulatory developments, especially regarding the PKL business licensing system. In addition, the local government through the Department of Industry and Trade has made various efforts to organize and empower street vendors, although its implementation still faces obstacles such as vendor compliance, limited business locations, and administrative constraints on licensing.